PEDAGOGICAL APPROACHES TO TEACHING HURDLE RACING RULES AND TECHNIQUES IN ATHLETICS - Badayev Rishad Rashidovich (Bright Mind Publishing, 2026)
This article provides a comprehensive analysis of the pedagogical methods for teaching the rules and technical execution of hurdle racing in athletics. Hurdling is a complex discipline that requires a synthesis of sprinting speed, rhythmic coordination, and technical precision. The study examines the progression of teaching from novice to advanced levels, emphasizing the integration of World Athletics (WA) regulations into the training process. Key areas of focus include the biomechanics of the hurdle clearance, safety protocols, and the specific rules regarding lane infringement and hurdle displacement. The article aims to equip physical education specialists and coaches with a structured methodology to effectively teach hurdling while ensuring adherence to international competition standards.
Keywords: Athletics, hurdling, pedagogy, competition rules, biomechanics, training methodology, physical education, sprint technique